2016
DOI: 10.1371/journal.pone.0157135
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Pulse Signal by Wave-Shape Function and Analyzing by Synchrosqueezing Transform

Abstract: We apply the recently developed adaptive non-harmonic model based on the wave-shape function, as well as the time-frequency analysis tool called synchrosqueezing transform (SST) to model and analyze oscillatory physiological signals. To demonstrate how the model and algorithm work, we apply them to study the pulse wave signal. By extracting features called the spectral pulse signature, and based on functional regression, we characterize the hemodynamics from the radial pulse wave signals recorded by the sphygm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Generally, the most common way to evaluate the hemodynamics in a vessel is to study the pulse wave signal (Fig. 3a) recorded at different locations (the most common from the arm, recording brachial pressure by the sphygmomanometer) 23 . As a matter of fact, this signal is useful for recording information about the blood pressure and the analysis of its waveform provides important clinical information.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the most common way to evaluate the hemodynamics in a vessel is to study the pulse wave signal (Fig. 3a) recorded at different locations (the most common from the arm, recording brachial pressure by the sphygmomanometer) 23 . As a matter of fact, this signal is useful for recording information about the blood pressure and the analysis of its waveform provides important clinical information.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding curve is characterized by the presence of two peaks, related to systole (SP) and diastole (DP), respectively, and a dicrotic notch (DN) between them. A distortion in the wave profile and, in particular, a variation of amplitude and position of these parameters are significant signs of an undesired variation in the patient hemodynamics, such as atherosclerosis or different heart dysfunctions 23 . In this respect, recording specific alterations of these signals on vascular grafts allows retrieving information on the graft status and highly predictive signs of prosthetic failures.…”
Section: Resultsmentioning
confidence: 99%
“…The harmonic three-phase model [11] reflects the waveform of the signal without taking into account its frequency and random component. Another option for pulse signal simulation is adaptive non-harmonic model [12], which does not take into account signal frequency. In addition to these shortcomings, the analysis of simulation models showed that they do not take into account changes in time and amplitude indicators due to the course of periodic medium-and long-term processes.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Among various challenges, one shared by many real-world signals is that the amplitude and frequency of each oscillatory component is time-varying, and the oscillatory pattern is usually not sinusoidal. With the advance of sensor technology, examples can be found in various areas, such as biomedicine [1][2][3], physics [4,5], to name but a few.…”
Section: Introductionmentioning
confidence: 99%